Overcoming CEP85L-ROS1, MKRN1-BRAF and MET amplification as rare, acquired resistance mutations to Osimertinib - Kian, Waleed; Krayim, Bilal; Alsana, Hadel; Giles, Betsy; Purim, Ofer; Alguayn, Wafeek; Alguayn, Farouq; Peled, Nir; Roisman, Laila C. (Frontiers in Oncology, 2023)
Lung cancer is the most common cancer-related cause of death worldwide, most of which are non-small cell lung cancers (NSCLC). Epidermal growth factor receptor (EGFR) mutations are common drivers of NSCLC. Treatment plans for NSCLC, specifically adenocarcinomas, rely heavily on the presence or absence of specific, actionable driver mutations. Liquid biopsy can guide the treatment protocol to detect the presence of various mechanisms of resistance to treatment.